Beyond conventional therapies: exploring the role of Pilates in neurological physical therapy – a review of the latest research - Maleszewska, Monika; Żmijewska, Aleksandra; Nowak, Gabriela; Sztybór, Mateusz; Piątkiewicz, Julia; Krzyżanowska, Maria; Wojtas, Mikołaj; Momot, Karol; Głogowska, Karen; Kapica, Marcin (Journal of Education, Health and Sport, 2024)
Pilates exercise method, characterized by its holistic approach, underscores core stability, strength, and flexibility, coupled with meticulous muscle control, optimal posture, and focused attention on breathing. Widely embraced in both general and clinical fitness realms, this study aims to evaluate the integration of Pilates into physical therapy practices for patients with neurological disorders. Existing studies indicate the potential efficacy of Pilates in diverse rehabilitation contexts. However, neurological disorders, specifically multiple sclerosis (MS) and Parkinson’s disease (PD), have been the primary focus. While systematic reviews and meta-analyses suggest Pilates as a plausible option in physiotherapy for PD and MS patients, a paucity of research on this subject necessitates a comprehensive review of recent original studies. Analysis of gathered data suggests that Pilates, when incorporated, may yield benefits for patients with various neurological disorders. Consideration of Pilates as a supplementary element to physical activity for those with PD and MS emerges as a reasonable proposition. The study also encourages contemplation of Pilates in rehabilitation research across a broader spectrum of neurological disorders. Subsequent investigations, incorporating relevant considerations, will contribute to a nuanced understanding of Pilates’ potential benefits and its comparative advantages over traditional interventions for neurological disorders.